Engine Electrified Cooling System: System and Control Design in Simulation Environment - Abhiskek, Makam (My University, 2019)
A cooling system is a vital part of any combustion engine. The cooling system helps maintain the temperature of the engine without allowing it to reach extreme values. A part of the power produced by the engine is used for the cooling system operations. Any savings in the energy consumption of the cooling system is used to improve the fuel efficiency of the vehicle. This master thesis deals with the development of an electric cooling system. This is done by replacing conventional parts of the cooling system with electric variants. Electrifying the cooling system creates additional degrees of freedom like control of pump speed and fan speed which are addressed by developing a control system and generating strategies to operate the components of the cooling system in the most energy efficient manner. The product of this thesis is a methodology to simulate the electric cooling system and its control system using PID controllers in Simulink. While tuning the controllers to perform as required was a challenging task, a lot of time and effort was invested in improving the robustness of the existing system model to yield good results. The developed methodology can be used to optimise the cooling system in a conventional vehicle, as well as, be adapted to the development of cooling systems in hybrid or electric vehicles. The recuperated energy while braking can be utilised to power the cooling system hence improving the performance and range of the vehicle.
Keywords: Electric cooling system; Control system; PID controllers; Electric pump; Electric fan; Thermostat; Three-way valve